Tales from a not-so-bratty little sister - Russell, Rachel Renée (Russell, Rachel Renée. Dork diaries, 2024)
"It's almost time for school to start again, and Nikki is a little worried -- but, as always, she has her BFFS to help. Only, it turns out her friends need Nikki's help. Nikki quickly gets overwhelmed and even starts feeling sick... which is when her little sister, Brianna, takes her chance to steal Nikki's diary! How much damage can Brianna do before Nikki is back on her feet?" --